Gestantes e uso de substâncias psicoativas: artigos psicanalíticos indexados no Qualis CAPES da Psicologia - Souza, Deborah Leite de Abreu (2023)
Considering the use of psychoactive substances by pregnant women, the social conditions of exploitation and violence to which this public is subjected stand out, reverberating in challenges and potentialities regarding the health care offered to them. Thus, the compulsive use of substances is understood as a possible symptom of this illness experience in which they are inserted. Given this situation, the objective was to analyze, through articles published in databases in the last 10 years, how the use of psychoactive substances by pregnant women is treated in the psychoanalytic field. The question is: do the approaches offer care proposals? Is there any relationship with harm reduction strategies for this public? We carried out a documentary analysis study, using a qualitative methodology, researching psychoanalytical articles indexed in Qualis Capes da Psicologia. As an instrument for collecting information, we carried out a search in the SCIELO and BVS databases and, finally, in the CAPES portal, with the following inclusion criteria: a) the text having been published in the last 10 years; b) be in Portuguese, c) refer to complete studies. The analyzes were carried out through theoretical-methodological assumptions of the discursive practices proposed by the philosopher Michel Foucault and dialogic maps proposed by Mary Jane Spink. We observed discussions about health care, in the psychosocial area and in collective health, reflecting on how this care can be better developed for women who abuse psychoactive substances and who are also mothers. We emphasize the importance of the ethical place of psychoanalysis in this discussion, understanding it as an important space to summon psychoanalysts to act in the construction of co-responsible care, aimed at people who abuse substances as a bet allied to HR, this possibility being raised in the current research.